Genome-wide analysis of the R2R3-MYB gene family in Spatholobus suberectus and identification of its function in flavonoid biosynthesis - Qin, Shuangshuang; Wei, Fan; Liang, Ying; Tang, Danfeng; Lin, Quan; Miao, Jianhua; Wei, Kunhua (Frontiers in Plant Science, 2023)
Spatholobus suberectus Dunn (S. suberectus), a plant species within the Leguminosae family, has a long history of use in traditional medicines. The dried stem of S. suberectus exhibits various pharmacological activities because it contains various flavonoids. Diverse functions in plants are associated with the R2R3-MYB gene family, including the biosynthesis of flavonoids.Nonetheless, its role remains unelucidated in S. suberectus. Therefore, the newly sequenced S. suberectus genome was utilized to conduct a systematic genome-wide analysis of the R2R3-MYB gene family. The resulting data identified 181 R2R3-SsMYB genes in total, which were then categorized by phylogenetic analysis into 35 subgroups. Among the R2R3-SsMYB genes, 174 were mapped to 9 different chromosomes, and 7 genes were not located on any chromosome. Moreover, similarity in terms of exon-intron structures and motifs was exhibited by most genes in the same subgroup. The expansion of the gene family was primarily driven by segmental duplication events, as demonstrated by collinearity analysis. Notably, most of the duplicated genes underwent purifying selection, which was depicted through the Ka/Ks analysis. In this study, 22 R2R3-SsMYB genes were shown to strongly influence the level of flavonoids. The elevated expression level of these genes was depicted in the tissues with flavonoid accumulation in contrast with other tissues through qRT-PCR data. The resulting data elucidate the structural and functional elements of R2R3-SsMYB genes and present genes that could potentially be utilized for enhancing flavonoid biosynthesis in S. suberectus.